Biostatistics methods used in celiac disease population studies - Iancu, Mihaela; Tilinca, Mariana; Cadariu, Andrei Achimas (International journal of celiac disease, 2014)
Introduction. Research on celiac disease is based on a descriptive and inferential variety of techniques that allow summarizing data and extrapolating the target population. The aim of this study was to identify descriptive and inferential statistical methods used in International Journal of Celiac Disease. Material and method. The sample of this study was defined based on all original articles published in the journal mentioned above in 2013-2014 period. We evaluated the descriptive statistics, the number and type of inferential statistical methods used. Results. Of the eight articles analyzed, one study was a randomzat clinical trial, the remaining studies were cross-sectional studies. The articles have used both quantitative and qualitative data. The indicator of central tendency on data was mean (n = 5, 62.5 %) or the median with interquartile range (n = 1, 12.5 %) and the dispersion of data was estimatedonly by the standard deviation in 5 studies (62.5 %). Quantitative data were used in raw form, except for one study using Z scores. Qualitative data were summarized using absolute and relative frequencies (n = 7, 87.5 %). The statistical software was mentioned in all studies. All articles except one used the inferential statistical methods or statistical tests. Most articles (87.5 %) used common tests as Student’s t- test (37.5), analysis of variance/covariance (25 %), Kruskal -Wallis test (12.5 %), χ2 test (50 %), and Fisher’s exact test (12.5 %). A specified significance level was noted in 62.5 % of the articles and the significance level was estimated in 6 studies (75 %). Conclusion. Results showed that a proper understanding of standard statistical methods leads to a proper interpretation of clinical research hypothesis. If necessary, the advanced statistical analysis should be performed by a multidisciplinary collaboration with specialists in biostatistics or epidemiology.
Keywords: Cross-Sectional Studies; dítě; mladiství; průřezové studie; Male; Celiac Disease; biostatistika; Randomized Controlled Trials as Topic; epidemiologické studie; lidé; Adolescent; ženské pohlaví; celiakie; Epidemiologic Studies; randomizované kontrolované studie jako téma; mužské pohlaví; Child; Humans; Biostatistics; Female